2007
DOI: 10.1080/09603100600771000
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting volatility in the financial markets: a comparison of alternative distributional assumptions

Abstract: This article analyses the volatility forecasting performance of the GARCH models based on various distributional assumptions in the context of stock market indices and exchange rate returns. Using rollover methods to construct the out-of-the-sample volatility forecasts, this study shows that the GARCH model combined with the logistic distribution, the scaled student's t distribution and the Riskmetrics model are preferable both in stock markets and foreign exchange markets. The exponential power and the mixtur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 23 publications
1
12
0
1
Order By: Relevance
“…The results show that the GARCH-N model is not outperformed by the competing models with returns innovations that allow for fat-tailed, leptokurtic and skewed characteristics. 9 These findings are consistent with the results of Chuang et al (2007), which showed that a complex distribution does not always outperform a simpler one. Nevertheless, our results contradict earlier findings of Wilhelmsson (2006), which argued that the GARCH model with a t-distribution improves volatility forecasts.…”
Section: Spa Test Results Of Distribution-type Modelssupporting
confidence: 95%
See 2 more Smart Citations
“…The results show that the GARCH-N model is not outperformed by the competing models with returns innovations that allow for fat-tailed, leptokurtic and skewed characteristics. 9 These findings are consistent with the results of Chuang et al (2007), which showed that a complex distribution does not always outperform a simpler one. Nevertheless, our results contradict earlier findings of Wilhelmsson (2006), which argued that the GARCH model with a t-distribution improves volatility forecasts.…”
Section: Spa Test Results Of Distribution-type Modelssupporting
confidence: 95%
“…The first category exploits symmetric GARCH models with alternative distributional assumptions to forecast volatility in various financial markets. Examples include Wilhelmsson (2006) and Chuang et al (2007). Wilhelmsson (2006) the predictive ability of the GARCH(1, 1) model when estimating S&P-500 index future returns with various error distributions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As pointed out in the previous literature (e.g., see [3,17,18]), the Student-t distribution as an assumption of distribution in GARCH model outperforms some alternative distributions such as the normal, exponential, and mixture of normal distributions. If has the Student-t distribution, the probability density functions of and are respectively given by, for t = 1, ..., T,…”
Section: Aparch(11) Model With Student-t Errorsmentioning
confidence: 86%
“…For our purposes, we will use the above 'classic' GARCH model with p ¼ q ¼ 1. The range of possible models has been investigated by several authors; for example, McMillan et al (2000) compare the forecast accuracy of a variety of GARCH formulations; Chuang et al (2007) investigate the effect on the forecasting accuracy of GARCH models using different density functions for z t .…”
Section: Generalised Autoregressive Conditional Heteroscedasticity Momentioning
confidence: 99%